Recycling method of waste ternary lithium battery

By performing discharge and disassembly, leaching and selective precipitation separation steps during the recycling of waste ternary lithium batteries, the problem of environmental pollution and metal resource separation difficulties in recycling of waste lithium batteries is solved, and efficient metal recycling and environmental protection are achieved.

CN120138345AActive Publication Date: 2025-06-13JIANGSU JIANSHEN ENVIRONMENTAL TECH CO LTD

Patent Information

Application Number
CN202510363331.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-26
Publication Date
2025-06-13
Estimated Expiration
2045-03-26

AI Technical Summary

Technical Problem

The prior art has environmental pollution and secondary pollution problems when recycling waste ternary lithium batteries, and it is difficult to efficiently separate and recover valuable metal resources such as manganese, cobalt, nickel and lithium.

Method used

The adhesive and conductive agent in the battery assembly are removed by discharge and disassembly steps, and the mixture of acid and oxidizing agent is leaching, and manganese, cobalt, nickel and lithium are separated by selective precipitation to achieve efficient recovery of these metals.

Benefits of technology

This method effectively avoids environmental pollution, improves the recovery rate of metal resources, and can obtain high-purity manganese dioxide, cobalt oxalate, nickel salt and lithium carbonate, which have good economic and social benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120138345A_ABST
    Figure CN120138345A_ABST
Patent Text Reader

Abstract

The invention relates to a method for recycling waste ternary lithium batteries. The recycling treatment method comprises the following steps: discharging and disassembling the waste battery to obtain a positive plate; removing the adhesive on the positive plate by adopting an organic solvent, and then separating to obtain a positive current collector and initial positive powder; removing the conductive agent in the initial positive electrode powder by adopting a flotation method to obtain pretreated positive electrode powder; a mixture of acid and an oxidizing agent is adopted as a leaching solution, the pretreated positive electrode powder is placed in the leaching solution to be subjected to leaching treatment, a leaching solution is obtained, and the leaching solution contains Mn < 2 + >, Co < 2 + >, Ni < 2 + > and Li < + >; and carrying out selective precipitation and extraction separation on the leachate to obtain manganese dioxide, cobalt salt, nickel salt and lithium salt so as to realize separation and recovery of manganese, cobalt, nickel and lithium in the positive electrode material of the lithium battery. According to the invention, effective recovery of the waste ternary lithium battery is effectively realized, and secondary pollution is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of recycling of waste ternary lithium batteries, and specifically relates to a method for recycling and treating waste ternary lithium batteries. Background Art

[0002] In recent years, lithium-ion batteries have been widely used in industries such as mobile electronic devices, new energy and hybrid vehicles, and grid energy storage due to advantages such as low self-discharge rate and long service life. The output of lithium-ion batteries has increased exponentially. Taking 2023 as an example, the total output of lithium batteries in China exceeded 940 GWh, a year-on-year increase of 25%, the total industry output value exceeded 1.4 trillion yuan, and the output of consumer, power, and energy storage lithium batteries from January to December was 80 GWh, 675 GWh, and 185 GWh respectively. The installed capacity of lithium batteries (including new energy vehicles and new energy storage) exceeded 435 GWh, and the export trade increased by more than 33% year-on-year.

[0003] At present, the number of retired commercial power lithium batteries on the market is huge. If they are directly discarded without recycling, it will cause a large amount of waste and environmental pollution. Most of the cost and the recyclable part of lithium batteries are concentrated in the positive electrode. The positive electrode material is generally lithium iron phosphate (LiFePO 4 , abbreviated as LFP), lithium cobalt oxide (LiCoO 2 , abbreviated as LCO), lithium nickel cobalt manganese (LiNi x CoyMn (1-x-y) O 2 , abbreviated as NCM), etc. Among them, the ternary material NCM has become the mainstream cathode material for new energy vehicles and the most common lithium battery positive electrode material on the market due to its advantages such as high energy density, high specific capacity, and long life. It is estimated that by 2050, the number of battery-powered passenger vehicles will exceed 100 million. Waste ternary lithium batteries contain a large amount of metals such as nickel, cobalt, manganese, and lithium, and have high recycling value. Since 2019, the prices of raw materials used to produce the cathodes of lithium-ion batteries, especially lithium and cobalt, have risen sharply for many years. The cost of the positive electrode material accounts for more than half of the total cost of all components. The weight ratios of cobalt, nickel, manganese, and lithium in NCM are 5-20%, 5-12%, 7-10%, and 2-5% respectively, and their contents exceed those of natural ores. If the valuable metal elements in waste lithium-ion batteries cannot be effectively recycled and reused, it will be a huge challenge to rely solely on natural mineral resources to meet the future market demand for lithium battery positive electrode materials. The recycling and utilization of valuable metals in waste lithium batteries helps to alleviate the depletion of strategic metal resources and reduce the cost of battery production, which is of great significance to the sustainable development of the environment and economy. In addition, waste lithium batteries also contain many harmful chemical substances, such as fluorides and organic substances. At the same time, effective recycling is also an urgent need to achieve the goal of carbon neutrality. Therefore, recycling waste ternary lithium batteries can effectively alleviate resource shortages and protect the environment.

[0004] At present, the common methods for recovering valuable metals from the cathode materials of waste lithium-ion batteries are mainly divided into pyrometallurgy and hydrometallurgy. Pyrometallurgy refers to directly heating the battery in a high-temperature smelting furnace, resulting in the burning of materials such as plastics, organic substances, and graphite. The high temperature promotes the reduction of metals such as cobalt, nickel, and copper, and these metals produce alloys with the help of reducing agents (such as aluminum foil, anode graphite, and introduced carbon). At the same time, lithium, manganese, and aluminum are entrained in the slag. Although pyrometallurgy can process waste lithium-ion batteries on a large scale, it is insufficient in recovering electrolytes, anode graphite, and valuable lithium. Moreover, pyrometallurgy not only requires a large amount of energy but also releases harmful gases, causing serious air pollution. Hydrometallurgy refers to dissolving the metals in the waste cathode powder into the liquid phase through solution soaking, and then separating and recovering the metals through precipitation, extraction, electrodeposition, etc. The hydrometallurgy process has the advantages of mild reaction conditions, environmental friendliness, and high recovery efficiency, and is the mainstream method in current laboratory and industrial production, but it will cause the generation of acidic or alkaline wastewater, leading to secondary environmental problems. Summary of the Invention

[0005] The purpose of the present invention is to provide a recycling method for waste ternary lithium batteries to achieve the effective recycling of waste ternary lithium batteries and reduce secondary pollution.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows: A recycling method for waste ternary lithium batteries includes the following steps: S1. Discharge and disassemble the waste battery to obtain a plastic shell, a negative electrode sheet, a separator, a positive electrode sheet, a battery cap, and an aluminum shell; S2. Remove the adhesive on the positive electrode sheet with an organic solvent and then separate to obtain a positive electrode current collector and initial positive electrode powder; S3. Use the flotation method to remove the conductive agent in the initial positive electrode powder to obtain pretreated positive electrode powder; S4. Use a mixture of an acid and an oxidant as the leaching solution, place the pretreated positive electrode powder in the leaching solution for leaching treatment to obtain a leachate, and the leachate contains Mn 2+ , Co 2+ , Ni 2+ and Li + ; S5. Use the selective precipitation method for the leachate for extraction and separation to obtain manganese dioxide, cobalt salts, nickel salts, and lithium salts, so as to achieve the separation and recovery of manganese, cobalt, nickel, and lithium in the cathode material of the lithium battery.

[0007] According to the above technical means, through the steps of discharging and disassembling, environmental pollution that may be caused during the treatment of waste batteries is effectively avoided. By removing the binder with organic solvents and removing the conductive agent by flotation, the positive electrode material can be efficiently separated, thereby improving the recovery rate of metal resources. The leaching solution is extracted and separated by the selective precipitation method, and manganese, cobalt, nickel and lithium can be accurately separated to achieve the effective recovery of these precious resources. Through the above steps, high-purity manganese dioxide, cobalt oxalate, nickel salt and lithium carbonate can be obtained, and these products can be used for the production of new battery materials or other industrial applications. This method not only reduces environmental pollution, but also can recover valuable metal resources, with good economic and social benefits.

[0008] Preferably, in S5, it includes: S51. Add potassium permanganate to the leaching solution, stir and react under the first temperature condition, keep warm and age, and filter to obtain manganese dioxide precipitate and the first filtrate; S52. Adjust the pH value of the first filtrate to neutral, add a mixed extractant, shake, and stand to obtain an oil phase containing Co 2+ and an aqueous phase containing Ni 2+ and Li + . The oil phase containing Co 2+ is subjected to back extraction to obtain an aqueous phase containing Co 2+ . The mixed extractant is a mixture of P507 extractant and sulfonated kerosene; S53. Adjust the aqueous phase containing Co 2+ to neutral, add sodium oxalate solution, stir and react, age, and filter to obtain cobalt oxalate precipitate; add sodium hydroxide solution to the aqueous phase containing Ni 2+ and Li + , stir and react, age, and filter to obtain nickel hydroxide and the third filtrate; S54. Add sodium carbonate solution to the third filtrate, stir and react, age, and filter to obtain lithium carbonate precipitate.

[0009] By adding potassium permanganate to the leaching solution, the manganese in the leaching solution is converted into manganese dioxide precipitate, thereby realizing the separation and recovery of manganese. By adjusting the pH value to neutral and using a specific mixed extractant (a mixture of P507 extractant and sulfonated kerosene), cobalt, nickel and lithium can be efficiently separated to achieve the enrichment of each metal. Reacting the sodium oxalate solution with the aqueous phase containing Co2+ can obtain high-purity cobalt oxalate precipitate, which is beneficial to the preparation of subsequent cobalt products. Containing Ni 2+ and Li +The aqueous phase can obtain nickel hydroxide and the third filtrate by adding sodium hydroxide solution, thus realizing the separation of nickel and lithium. Finally, adding sodium carbonate solution to the third filtrate can efficiently precipitate lithium carbonate from the solution, which is beneficial to the recovery and utilization of lithium resources. Through temperature control, pH adjustment and the use of extractants, the whole process realizes the efficient separation and recovery of various metals and improves the resource utilization rate. This method has clear operation steps and mild reaction conditions, which is beneficial to industrial application and environmental friendliness.

[0010] Among them, the P507 extractant is a colorless or light yellow transparent oily liquid, and its structural formula is .

[0011] Preferably, in the S51, the molar ratio of potassium permanganate to Mn in the leaching solution is 1-2. 2+ is 1 to 2.

[0012] Preferably, in the S51, the first temperature is 50-70 °C.

[0013] Preferably, in the S53, the molar ratio of sodium oxalate to the aqueous phase containing Co 2+ is calculated as n[C 2 O 4 2- : n[Co 2+ is 0.8-1.2.

[0014] Preferably, in the S53, adding sodium hydroxide solution to the aqueous phase containing Ni 2+ and Li + makes the pH value of the solution 8-12.

[0015] Preferably, in the S54, the molar ratio of sodium carbonate to Li in the third filtrate + is calculated as n[CO 3 2- : n[Li + is 0.5-0.9.

[0016] Preferably, the S5 includes: S501. Add potassium permanganate to the leaching solution, stir and react under the condition of the first temperature, keep warm and age, then filter to obtain manganese dioxide precipitate and the first filtrate; S502. Dissolve dimethylglyoxime (DMG) in ethanol, then add the first filtrate, adjust the pH to acidic, stir and react, keep warm and age, then filter to obtain dimethylglyoxime nickel precipitate and the fifth filtrate; S503. Adjust the pH value of the fifth filtrate to neutral, add the mixed extractant, shake and let it stand to obtain the oil phase containing Co 2+ and the aqueous phase containing Li+ The aqueous phase contains Co 2+ The oil phase is subjected to back extraction to obtain an aqueous phase containing Co 2+ The mixed extractant is a mixture of P507 extractant and sulfonated kerosene; S504, adjust the aqueous phase containing Co 2+ to neutrality, add sodium oxalate solution, stir and react, age, filter to obtain cobalt oxalate precipitate; S505, add sodium carbonate solution to the aqueous phase containing Li + and stir and react, age, filter to obtain lithium carbonate precipitate.

[0017] The use of potassium permanganate can effectively oxidize the impurities in the leaching solution and improve the purity of the manganese dioxide precipitate. Dimethylglyoxime (DMG) as a precipitant can efficiently form a precipitate with nickel ions, thus realizing the separation and recovery of nickel. By adjusting the pH value to acidic, the precipitation reaction conditions of nickel dimethylglyoxime can be optimized to improve the precipitation efficiency and purity. Using a mixed extractant (P507 extractant and sulfonated kerosene) for extraction can effectively separate cobalt and lithium and achieve the separate recovery of the two metals. The reaction of sodium oxalate solution with the aqueous phase containing Co 2+ can obtain high-purity cobalt oxalate precipitate, providing raw materials for the preparation of subsequent cobalt products. The reaction of sodium carbonate solution with the aqueous phase containing Li + can efficiently prepare lithium carbonate precipitate, providing an effective way for the recovery of lithium resources. In the whole process, by adjusting the pH value and temperature conditions, the reaction process can be optimized to improve the metal recovery rate and product purity. This method realizes the efficient recovery of multiple metals through chemical reactions and separation technologies and has high industrial application value.

[0018] Preferably, in the S501, the molar ratio of potassium permanganate to Mn 2+ in the leaching solution is 1 to 2.

[0019] Preferably, in the S501, the first temperature is 50 to 70 °C.

[0020] Preferably, in the S502, the molar ratio of dimethylglyoxime (DMG) to the first filtrate is 1.6 to 2.4 in terms of n[DMG]:n[Ni 2+ .

[0021] Preferably, in the S502, the pH value is 1 to 5.

[0022] Preferably, in the S504, the molar ratio of sodium oxalate to the aqueous phase containing Co 2+ is in terms of n[C 2 O 4 2- :n[Co 2+It is counted as 0.8 to 1.2.

[0023] Preferably, in the step S505, the molar ratio of sodium carbonate to the aqueous phase containing Li + is counted as n[CO 3 2- : n[Li + and is counted as 0.5 to 0.9.

[0024] Preferably, in the step S2, the organic solvent is selected from dimethylacetamide (DMAC), and the solid-liquid ratio of the positive electrode sheet to dimethylacetamide (DMAC) is 25 to 45 g / L.

[0025] Preferably, in the step S2, ultrasonic assistance is combined to remove the adhesive on the positive electrode sheet. The power of the ultrasonic wave is 800 to 900 W, and the time of the ultrasonic wave is 30 to 110 min.

[0026] Preferably, in the step S2, it further includes recycling the dimethylacetamide (DMAC) solution separated after removing the adhesive on the positive electrode sheet by using an organic solvent. The recycling method is: distilling the dimethylacetamide (DMAC) solution under the condition that the temperature is 175 to 185 °C to obtain a dimethylacetamide (DMAC) distillate, and the dimethylacetamide (DMAC) distillate is recycled to remove the adhesive on the positive electrode sheet.

[0027] Preferably, in the step S3, dibromomethane is used as a flotation agent to remove the conductive agent in the initial positive electrode powder.

[0028] Advantages of the present invention: The recycling and treatment method of the waste ternary lithium battery of the present invention effectively avoids the possible environmental pollution caused by waste batteries during the treatment process through the discharging and disassembling steps. By using an organic solvent to remove the adhesive and the flotation method to remove the conductive agent, the positive electrode material can be efficiently separated, thereby improving the recovery rate of metal resources. The selective precipitation method is used to extract and separate the leaching solution, and manganese, cobalt, nickel and lithium can be accurately separated to realize the effective recovery of these precious resources. Through the above steps, high-purity manganese dioxide, cobalt oxalate, nickel salt and lithium carbonate can be obtained, and these products can be used for the production of new battery materials or other industrial applications. This method not only reduces environmental pollution, but also can recycle valuable metal resources, has good economic and social benefits, and has the value of popularization and application in the field of waste ternary lithium battery recycling technology. Description of the drawings

[0029] Figure 1 It is the first flow chart of the recycling and treatment method of the waste ternary lithium battery; Figure 2 It is the physical diagram of the initial positive electrode powder obtained in Example 1; Figure 3 It is a physical diagram of separating NCM and acetylene carbon black with dibromomethane under static state; Figure 4 It is a physical diagram of the first precipitate obtained in Example 1; Figure 5 It is an XRD diagram of the first precipitate obtained in Example 1; Figure 6 It is a physical diagram of the second precipitate obtained in Example 1; Figure 7 It is an XRD diagram of the second precipitate obtained in Example 1; Figure 8 It is a physical diagram of the third precipitate obtained in Example 1; Figure 9 It is an XRD diagram of the third precipitate obtained in Example 1; Figure 10 It is a physical diagram of the fourth precipitate obtained in Example 1; Figure 11 It is an XRD diagram of the fourth precipitate obtained in Example 1; Figure 12 It is a diagram of the influence result of solid-liquid ratio on the exfoliation effect; Figure 13 It is a diagram of the influence result of ultrasonic time on the exfoliation effect; Figure 14 It is a diagram of the influence result of sulfuric acid concentration on the leaching effect; Figure 15 It is a diagram of the influence result of hydrogen peroxide volume fraction on the leaching effect; Figure 16 It is a diagram of the influence result of solid-liquid ratio on the leaching effect; Figure 17 It is a diagram of the influence result of leaching treatment time on the leaching effect; Figure 18 It is a diagram of the influence result of leaching treatment temperature on the leaching effect; Figure 19 It is a diagram of the influence result of potassium permanganate addition amount on the first precipitation effect; Figure 20 It is a diagram of the influence result of pH value on the extraction effect; Figure 21 It is a diagram of the influence result of oil-water ratio on the extraction effect; Figure 22 It is a diagram of the influence result of oscillation time on the extraction effect; Figure 23 It is a diagram of the influence result of dilution multiple on the extraction effect; Figure 24 It is a diagram of the influence result of sodium oxalate addition amount on the second precipitation effect; Figure 25 Graph showing the effect of pH on the third precipitation result; Figure 26 Graph showing the effect of the amount of sodium carbonate on the fourth precipitation result; Figure 27 Second flowchart of the recycling method for waste ternary lithium batteries; Figure 28 Physical picture of the fifth precipitate obtained in Example 10; Figure 29 XRD pattern of the fifth precipitate obtained in Example 10; Figure 30 Graph showing the effect of the addition amount of DMG on the ion precipitation rate; Figure 31 Graph showing the effect of pH value on the ion precipitation rate; Figure 32 For Na 2 S 2 O 8 Graph showing the effect of the addition amount on the precipitation effect of Mn 2+ ; Figure 33 Graph showing the effect of pH on the precipitation effect of Mn 2+ ; Among them, 1 - carbon black; 2 - dibromomethane; 3 - pretreated positive electrode powder; Detailed implementation mode

[0030] The following will describe the implementation mode of the present invention with reference to preferred embodiments. Those skilled in the art can clearly understand other advantages and effects of the present invention from the content described in this specification. The present invention can also be implemented or applied through other different specific implementation modes. Various details in this specification can also be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention. It should be understood that the preferred embodiments are only for explaining the present invention, rather than for limiting the protection scope of the present invention.

[0031] Example 1 As Figure 1 shown, a recycling method for waste ternary lithium batteries includes the following steps: S1. Discharging and manual disassembly: Discharging and disassembling the waste battery to obtain a plastic shell, a negative electrode sheet, a separator, a positive electrode sheet, a battery cap, and an aluminum outer shell, specifically including: Connect the positive and negative electrodes of the waste battery to a sliding rheostat, and then connect a 1A current limiter in series in the circuit to prevent excessive power. After discharging for about 24 hours, the battery voltage drops to 0.32V, and the discharging ends and disassembly begins. Place the discharged battery in a fume hood, use a small electric cutting knife to cut open the shell, and then manually separate six components: the plastic shell, the negative electrode sheet, the separator, the positive electrode sheet, the battery cap, and the aluminum shell. The weights of each part are shown in Table 1; Table 1 Weights and Proportions of Each Part of a Single Lithium Battery S2. After removing the adhesive on the positive electrode sheet with an organic solvent and separating, the positive electrode current collector and the initial positive electrode powder are obtained. Specifically, it includes: Soak the positive electrode sheet obtained in S1 with dimethylacetamide (DMAC), and combine it with ultrasonic assistance to remove the adhesive (polyvinylidene fluoride, i.e., PVDF) on the positive electrode sheet, filter, and obtain the positive electrode current collector (aluminum foil), the initial positive electrode powder, and the dimethylacetamide (DMAC) soaking solution. Among them, the solid-liquid ratio of dimethylacetamide (DMAC) to the positive electrode sheet is 35 g / L, the ultrasonic power is 860 W, and the ultrasonic time is 110 min. The physical diagram of the obtained initial positive electrode powder is as Figure 2 shown; S3. Use the flotation method to remove the conductive agent in the initial positive electrode powder to obtain the pretreated positive electrode powder. Specifically, it includes: Use the organic solvent dibromomethane as the flotation agent. Add the initial positive electrode powder obtained in S2 to dibromomethane, stir evenly, and then let it stand for 2 h. As Figure 3 shown, in the standing state, the upper layer is carbon black 1, the middle layer is dibromomethane 2, and the lower layer is the pretreated positive electrode powder 3. Use a dropper to suck out the carbon black 1 in the upper layer, and then obtain the pretreated positive electrode powder 3 and dibromomethane 2 through filtration separation to achieve three-phase separation. The dibromomethane 2 obtained by filtration separation is recycled; S4. Use a mixture of an acid and an oxidant as the leaching solution, and place the pretreated positive electrode powder in the leaching solution for leaching treatment to obtain a leaching solution. The leaching solution contains Mn 2+ , Co 2+ , Ni 2+ and Li + . Specifically, it includes: Use a mixture of sulfuric acid and hydrogen peroxide as the leaching solution, place the pretreated positive electrode powder 3 obtained in S3 in the leaching solution for leaching treatment to obtain a leaching solution. The leaching solution contains Mn 2+ , Co 2+ , Ni 2+ and Li + , Among them, in the leaching solution, the sulfuric acid concentration is 2.5 M, and the volume percentage content of hydrogen peroxide is 6%; the solid-liquid ratio of the leaching solution to the pretreated positive electrode powder 3 is 15 g / L, the temperature of the leaching treatment is 60 °C, and the time of the leaching treatment is 120 min; S5. For the leaching solution, selective precipitation method and extraction separation are carried out to obtain manganese dioxide, cobalt oxalate, nickel hydroxide and lithium carbonate, so as to realize the separation and recovery of manganese, cobalt, nickel and lithium in the cathode material of the lithium battery, specifically including: S51. Add the leaching solution obtained in S4 and potassium permanganate into the reaction vessel, then place the reaction vessel on a magnetic stirrer, set the heating temperature to 60 °C and the stirring speed to 200 r / min. After reacting for 0.5 h, keep it warm and age for 1 h, and then filter it using a suction filtration instrument to obtain the first precipitate and the first filtrate. After filtration, rinse the reaction vessel and the first precipitate with hot water 3-4 times, and merge the rinsing solution into the first filtrate; among them, the addition amount of potassium permanganate is based on Mn 2+ in the leaching solution, and n[Mn 2 + : n[KMnO 4 is 1:1.5; the physical diagram of the obtained first precipitate is as shown in Figure 4 ; the first precipitate is analyzed by XRD, and the results are as shown in Figure 5 ; it can be analyzed from Figure 5 that the peak positions and peak heights of the XRD pattern of the first precipitate basically coincide with those in the manganese dioxide standard card, thus proving that the precipitated first precipitate is mainly MnO 2 , and the crystal form is relatively complete; the model of the X-ray diffractometer is X'Pert PRO MPD, the analysis conditions are Cu target, the test angle 2θ is 5°~90°, and the scanning speed is 2° / min; S52. Adjust the pH value of the first filtrate obtained in S51 to 6.5, then add a mixed extractant, shake for 8 min, let it stand for liquid separation, and obtain an oil phase and an aqueous phase containing Co 2+ to realize the separation of Co 2+ from Ni 2+ and Li + . After extraction, use 1.5 M sulfuric acid solution to back-extract the oil phase containing Co 2+ , the ratio of the oil phase to the aqueous phase is 1:1, and the shaking time is 8 min, so that Co 2+ enters the aqueous phase from the organic phase to obtain an aqueous phase containing Co 2+ ; among them, the extractant is a mixed extractant with a volume ratio of P507 extractant to sulfonated kerosene of 1:4, and the mixed extractant is saponified before use; the oil-water ratio (the volume ratio of the extractant to the first filtrate) is 1:1; S53. The Co-containing 2+The aqueous phase is placed in a reaction vessel, and dilute sulfuric acid or sodium hydroxide solution is added to adjust the pH to neutral. Then, sodium oxalate solution is added. Next, the reaction vessel is placed on a magnetic stirrer, the temperature is set at room temperature, the stirring speed is 200 r / min, and after reacting for 0.5 h, it is aged for 1 h. Then, a suction filtration instrument is used for filtration to obtain a second precipitate and a second filtrate. After filtration, the reaction vessel and the second precipitate are rinsed 3 - 4 times with ultrapure water, and the rinsing liquid is combined into the second filtrate; among them, the addition amount of sodium oxalate is based on Co 2+ in the aqueous phase containing Co 2+ and n[C 2 O 4 2- : n[Co 2+ is 1.1:1; the physical picture of the obtained second precipitate is as shown in Figure 6 . The second precipitate is dried in an oven at 50 °C, and finally pink cobalt oxalate powder is obtained; the second precipitate is analyzed by XRD, and the result is as shown in Figure 7 . It can be analyzed from Figure 7 that the second precipitate is CoC 2 O 4 ∙H 2 O. The peak positions and heights of several main peaks are basically the same as those of the standard card, and there are no impurity peaks, so it can be determined that a single-phase CoC 2 O 4 ∙H 2 O is formed by the reaction; S54. The aqueous phase in S52 is placed in a reaction vessel, and sodium hydroxide solution is added to make the pH value 11. Then, the reaction vessel is placed on a magnetic stirrer, the temperature is set at room temperature, the stirring speed is 200 r / min, and after reacting for 0.5 h, it is aged for 1 h. Then, a suction filtration instrument is used for filtration to obtain a third precipitate and a third filtrate. After filtration, the reaction vessel and the third precipitate are rinsed 3 - 4 times with ultrapure water, and the rinsing liquid is combined into the third filtrate; the physical picture of the obtained third precipitate is as shown in Figure 8 . The third precipitate is dried in an oven at 50 °C, and finally green nickel hydroxide powder is obtained; the third precipitate is analyzed by XRD, and the result is as shown in Figure 9 . It can be analyzed from Figure 9 that the peak positions and peak heights of the third precipitate are basically consistent with the standard spectrum of nickel hydroxide, and there are relatively few impurity peaks, indicating that the product is relatively pure Ni(OH) 2 ; S55. Place the third filtrate obtained in S54 in a reaction vessel, add sodium carbonate solution, then place the reaction vessel on a magnetic stirrer, set the temperature to room temperature and the stirring speed to 200 r / min. After reacting for 0.5 h, age for 1 h, then filter using a suction filtration instrument to obtain a fourth precipitate and a fourth filtrate. After filtration, rinse the reaction vessel and the fourth precipitate 3 - 4 times with ultrapure water at 90 °C, and incorporate the rinsing liquid into the fourth filtrate; The physical diagram of the obtained fourth precipitate is as shown in Figure 10 shown. The fourth precipitate is white lithium carbonate powder; The fourth precipitate was analyzed by XRD, and the results are as shown in Figure 11 shown; It can be analyzed from Figure 11 that the fourth precipitate is Li 2 CO 3 , the peak positions and heights of several main peaks are basically the same as those of the standard card, and there are no impurity peaks, so it can be determined that the reaction produced a single-phase Li 2 CO 3 .

[0032] After a series of separation, extraction, and precipitation experiments, the final recovery rates of the four metals, lithium, nickel, cobalt, and manganese, are shown in Table 2.

[0033] Table 2 Final recovery rates of each metal Example 2 In this example, the effects of the solid-liquid ratio of dimethylacetamide (DMAC) to the positive electrode sheet and the ultrasonic time on the purity of the positive electrode current collector (aluminum foil) and the stripping efficiency of the binder were studied. The settings of the solid-liquid ratio and ultrasonic time, as well as the test results, are shown in Table 3, Figure 12 and Figure 13 shown. The steps and parameter conditions in the remaining S1 and S2 are the same as those in Example 1.

[0034] Table 3 Effects of solid-liquid ratio and ultrasonic time on stripping effect As can be seen from Table 2 and Figure 12 , as the solid-liquid ratio increases, the purity and stripping efficiency of the positive electrode current collector (aluminum foil) both decrease. As can be seen from Table 2 and Figure 13 , as the ultrasonic time increases, the purity and stripping efficiency of the positive electrode current collector (aluminum foil) gradually increase, and when the ultrasonic time is 110 min, they can reach 93.60% and 98.90% respectively.

[0035] Example 3 The recovery treatment of the dimethylacetamide (DMAC) immersion solution obtained in S2 of Example 1 includes: Use a distillation apparatus to control the distillation temperature between 180°C ± 5°C and distill until there is no residual liquid at the bottom of the flask. The volume of the solution before distillation is 780 mL, and after distillation it is 760 mL, with a recovery rate of 96.15%. There is a yellow film-like PVDF solid at the bottom of the flask after distillation.

[0036] Soak the initial positive electrode powder obtained in S2 of Example 1 with DMAC for 2 h, filter and then distill the resulting dimethylacetamide (DMAC) soaking solution again. There is no residual yellow solid at the bottom of the flask after evaporation to dryness, thus proving that polyvinylidene fluoride (PVDF) on the positive electrode sheet has completely dissolved in DMAC during the ultrasonic process and there is no residue on the surface of the positive electrode powder.

[0037] Use the DMAC obtained by distillation recovery to conduct an aluminum foil stripping test under the same conditions as S1 and S2 in Example 1. The purity of the positive electrode current collector (aluminum foil) obtained is 94.6%, and the stripping efficiency is 97.2%, thus proving that the separation effect of the DMAC after distillation is still very good and can be recycled.

[0038] Example 4 In this example, the concentrations of sulfuric acid and hydrogen peroxide in the leaching solution, the solid-liquid ratio of the leaching solution to the pretreated positive electrode powder 3, and the temperature and time of the leaching treatment on the leaching rates of Mn 2+ , Co 2+ , Ni 2+ and Li + were studied. The steps and parameter conditions in the remaining S1, S2, and S3 are the same as those in Example 1. After each reaction ends, the volume of the leaching solution is fixed to 50 mL, and after dilution, the concentrations of each ion are tested using ICP. The results are as Figures 14 to 18 shown. Each time, three parallel samples are measured, Figures 14 to 18 and it is the average value of three parallel samples for each ion.

[0039] It can be analyzed from Figures 14 to 18 that the concentrations of sulfuric acid and hydrogen peroxide in the leaching solution, the solid-liquid ratio of the leaching solution to the pretreated positive electrode powder, and the temperature and time of the leaching treatment all have an impact on the leaching rates of Mn 2+ , Co 2+ , Ni 2+ and Li + . Among them, when the leaching time is 120 min, the sulfuric acid concentration is 2.5 M, the reaction temperature is 60°C, the hydrogen peroxide volume fraction is 6%, and the solid-liquid ratio is 15 g / L, the Mn 2+ , Co 2+ , Ni 2+ and Li +The leaching rates of the four metal ions are 99.8%, 99.6%, 99.9% and 99.1% respectively. The contents of the four metal ions in the leaching solution are 0.761 g / L, 5.213 g / L, 2.016 g / L and 2.667 g / L respectively.

[0040] Example 5 In this example, the effect of the addition amount of KMnO 4 on the precipitation effect of Mn 2+ was studied. The steps and parameter conditions in the rest of S1, S2, S3, S4 and S51 were the same as those in Example 1. The first filtrate in S51 obtained each time was fixed to 100 mL respectively, and the nickel, cobalt, manganese and lithium contents in it were tested by ICP-MS. Each group of experiments was carried out in triplicate, and the test results are as Figure 19 shown. From Figure 19 analysis, it can be seen that when the value of n(Mn 2+ :KMnO 4 ) is between 1 and 1.5, the content of manganese in the solution continuously decreases. At this time, most of the manganese in the solution exists in the form of Mn 2+ , because the addition amount of potassium permanganate is small and not enough to completely precipitate the Mn 2+ in the solution; while when the value of n(Mn 2+ :KMnO 4 ) is between 1.5 and 2, the content of manganese in the solution continuously increases. At this time, most of the manganese in the solution exists in the form of MnO 4 - , because an excessive amount of potassium permanganate is added to the solution, resulting in the remaining of MnO 4 - , and the content of cobalt decreases slightly, which may be due to the reaction with MnO 4 - . During the whole reaction process, the contents of lithium and nickel do not decrease significantly.

[0041] Among them, the calculation formula of the metal leaching rate η is as shown in Equation Ⅰ: (Ⅰ) In Equation Ⅰ, C 1 represents the concentration of metal ions in the filtrate (mg / L); V 1 represents the volume of the filtrate (L); C 2 represents the concentration of metal ions in the filter residue (mg / L); V 2 represents the volume of the filter residue dissolution solution (L).

[0042] The calculation formula of the metal precipitation rate P Me is as shown in Equation Ⅱ: (II) In Formula II, C3 represents the concentration of metal ions in the solution before precipitation (mg / L); C4 represents the concentration of metal ions in the solution after precipitation (mg / L).

[0043] Example 6 In this example, the effects of the pH value of the first filtrate, the oil-water ratio (the volume ratio of the extractant to the first filtrate), the oscillation time, and the volume ratio of P507 extractant to sulfonated kerosene in the mixed extractant on the extraction effect were studied. The steps and parameter conditions in the remaining S1, S2, S3, S4, S51, and S52 were the same as those in Example 1. After each aqueous phase obtained in S52 was diluted, the concentrations of lithium, nickel, and cobalt in the aqueous phase were measured using ICP-MS, and the extraction rate was calculated. The results are as follows Figures 20 to 23 shown.

[0044] Among them, the extraction rate E Me and the stripping rate are calculated according to Formulas III and IV as follows; (III) (IV) In Formulas III and IV, C a represents the concentration of metal ions in the aqueous phase after extraction (mg / L); V a represents the volume of the aqueous phase after extraction (L); C b represents the concentration of metal ions in the solution before extraction (mg / L); V b represents the volume of the solution before extraction (L); C m represents the concentration of metal ions in the solution after stripping (mg / L); V m represents the volume of the solution after stripping (L); C n represents the concentration of metal ions in the organic phase before stripping (mg / L); V n represents the volume of the organic phase before stripping (L).

[0045] It can be analyzed from Figure 20 that as the pH increases, the extraction rates of all three metals increase continuously. This is because H +The reduction can promote the reaction and thus drive the extraction process. When pH = 4.5, the extraction rates of cobalt, nickel, and lithium are 63.72%, 10.44%, and 1.66% respectively. When the pH increases to 6.5, the extraction rates of cobalt, nickel, and lithium are 95.30%, 22.03%, and 3.19% respectively. Most of the cobalt in the solution is extracted into the organic phase, and at the same time, part of the nickel and a small part of the lithium are also extracted. When the pH continues to increase to 7.0, the extraction rate of cobalt slows down, only increasing from 95.30% to 95.87%, while the extraction rate of nickel increases from 20.54% to 36.38%, and the extraction rate of lithium increases from 3.19% to 4.48%. Thus, simply increasing the pH cannot completely extract cobalt, and it will also cause a large amount of nickel to enter the organic phase, reducing the purity of cobalt.

[0046] Analysis shows that Figure 21 the oil-water ratio has a great influence on the extraction rate of metals. Under the condition that other conditions remain unchanged, the extraction rate E increases with the increase of O / A. When O / A = 0.5, the extraction rates of cobalt, nickel, and lithium are 71.73%, 1.15%, and 0.99% respectively. As O / A increases, the extraction rates of the three metals all increase. When O / A = 1.0, the extraction rates of cobalt, nickel, and lithium are 95.31%, 22.03%, and 3.19% respectively. As O / A continues to increase, the extraction rate of cobalt slows down and no longer increases significantly, while the extraction rates of nickel and lithium increase greatly, which will greatly reduce the purity of cobalt in the organic phase. Therefore, the optimal oil-water ratio is 1:1.

[0047] Analysis shows that Figure 22 as the shaking time increases, the contact between the organic phase and the aqueous phase will be more sufficient. Therefore, the extraction rates E of the three metals all increase with the prolongation of the shaking time, and the extraction rates of cobalt and nickel are more significantly affected by the shaking time. When the shaking time is 2 min, the extraction rates of cobalt, nickel, and lithium are 51.55%, 10.96%, and 0.54% respectively. When the shaking time is 8 min, the extraction rates of cobalt, nickel, and lithium are 95.31%, 22.03%, and 3.19% respectively.

[0048] Analysis shows that Figure 23Analysis shows that, compared with the other three factors, the dilution ratio of P507 (i.e., the volume ratio of P507 to sulfonated kerosene) has a smaller impact on the extraction rates of the three metals. However, it can also be seen that as the dilution ratio of P507 increases, the extraction rates of the three metals all show a decreasing trend. This is because the more P507 there is, the more it can promote the extraction reaction. When the dilution ratio is 5 (i.e., the volume ratio of P507 to sulfonated kerosene is 1:5), the extraction rates of cobalt, nickel, and lithium are 89.52%, 19.46%, and 2.6% respectively. When the dilution ratio drops to 4, the extraction rates of cobalt, nickel, and lithium are 95.31%, 22.03%, and 3.19% respectively. As the dilution ratio continues to decrease, the extraction rate of cobalt tends to be stable, while the extraction rate of nickel increases significantly.

[0049] Example 7 In this example, the effect of the addition amount of sodium oxalate on the Mn 2+ precipitation effect was studied. The steps and parameter conditions in the rest of S1, S2, S3, S4, S51, S52, and S53 were the same as those in Example 1. The second filtrate in S53 obtained each time was fixed to 100 mL, and the cobalt content in it was measured by ICP-MS, and the precipitation rate of cobalt was calculated. Each group of experiments was carried out in triplicate, and the results are as Figure 24 shown.

[0050] From Figure 24 analysis, it can be seen that as the addition amount of sodium oxalate continuously increases, the Co 2+ precipitation rate is also continuously increasing. When n[C 2 O 4 2- :n[Co 2+ =0.8:1, the Co 2+ precipitation rate is 73.3%. When n[C 2 O 4 2- :n[Co 2+ rises to 1.1:1, the Co 2+ precipitation rate can reach 97.87%. When n[C 2 O 4 2- :n[Co 2+ =1.2:1, the Co 2+ precipitation rate is 98.32%, and there is no obvious increase anymore.

[0051] Example 8 In this example, the effect of pH value on Ni 2+Effect on precipitation, and the steps and parameter conditions in the remaining S1, S2, S3, S4, S51, S52, and S54 are the same as those in Example 1. The third filtrate in S54 obtained each time was fixed to 100 mL, and the nickel and lithium contents were measured using ICP-MS, and the precipitation rates of nickel and lithium were calculated. Each group of experiments was carried out in triplicate, and the results are as Figure 25 shown.

[0052] It can be analyzed from Figure 25 that as the pH increases from 8 to 11, the precipitation rate of nickel also increases from 86.1% to 98.17%. When the pH is increased to 12, the precipitation rate of nickel is 98.70%, without much increase. At the same time, although the pH has been increasing, the loss rate of lithium has been stable below 0.5%, indicating that the process of precipitating nickel does not affect lithium, and it also indicates that the recovered nickel hydroxide has a high purity.

[0053] Example 9 In this example, the effect of the dosage of sodium carbonate on the precipitation of Li + was studied, and the steps and parameter conditions in the remaining S1, S2, S3, S4, S51, S52, S54, and S55 are the same as those in Example 1. The fourth filtrate in S55 obtained each time was fixed to 100 mL, and the lithium content was measured using ICP-MS, and the precipitation rate of lithium was calculated. Each group of experiments was carried out in triplicate, and the results are as Figure 26 shown.

[0054] It can be analyzed from Figure 26 that when n[CO 3 2- :n[Li + =0.5, the precipitation rate of lithium is only 64.45%. With the continuous addition of sodium carbonate, the precipitation rate of lithium is also getting higher and higher. When n[CO 3 2- :n[Li + =0.8, the precipitation rate of lithium rises to 95.38%, while when n[CO 3 2- :n[Li + continues to increase to 0.9, the precipitation rate of lithium does not increase significantly, being 96.26%.

[0055] Example 10 As Figure 27 shown, a method for recycling and treating waste ternary lithium batteries includes the following steps: S1. Discharging and manual disassembly: Discharge and disassemble the waste battery to obtain a plastic shell, a negative electrode sheet, a separator, a positive electrode sheet, a battery cap, and an aluminum outer shell, specifically including: Connect the positive and negative electrodes of the waste battery to a sliding rheostat, and then connect a 1A current limiter in series in the circuit to prevent excessive power. After discharging for about 24 hours, the battery voltage drops to 0.32V, and the discharge ends and disassembly begins. Place the discharged battery in a fume hood, use a small electric cutting knife to cut open the shell, and then manually separate six components: the plastic shell, the negative electrode sheet, the separator, the positive electrode sheet, the battery cap, and the aluminum shell; S2. After removing the adhesive on the positive electrode sheet using an organic solvent and separating, the positive current collector and the initial positive powder are obtained. Specifically, it includes: Soak the positive electrode sheet obtained in S1 with dimethylacetamide (DMAC), and combine it with ultrasonic assistance to remove the adhesive (polyvinylidene fluoride, i.e., PVDF) on the positive electrode sheet, and filter to obtain the positive current collector (aluminum foil), the initial positive powder, and the dimethylacetamide (DMAC) soaking solution. Among them, the solid-liquid ratio of dimethylacetamide (DMAC) to the positive electrode sheet is 35 g / L, the ultrasonic power is 860 W, and the ultrasonic time is 110 min; S3. Use the flotation method to remove the conductive agent in the initial positive powder to obtain the pretreated positive powder. Specifically, it includes: Use the organic solvent dibromomethane as the flotation agent. Add the initial positive powder obtained in S2 to dibromomethane, stir evenly and then let it stand for 2 hours. As Figure 3 shown, in the standing state, the upper layer is carbon black 1, the middle layer is dibromomethane 2, and the lower layer is the pretreated positive powder 3. Use a dropper to suck out the carbon black 1 in the upper layer, and then obtain the pretreated positive powder 3 and dibromomethane 2 through filtration separation to achieve three-phase separation. The dibromomethane 2 obtained by filtration separation is recycled; S4. Use a mixture of an acid and an oxidant as the leaching solution, and place the pretreated positive powder in the leaching solution for leaching treatment to obtain a leaching solution. The leaching solution contains Mn 2+ , Co 2+ , Ni 2+ and Li + . Specifically, it includes: Use a mixture of sulfuric acid and hydrogen peroxide as the leaching solution, and place the pretreated positive powder 3 obtained in S3 in the leaching solution for leaching treatment to obtain a leaching solution. The leaching solution contains Mn 2+ , Co 2+ , Ni 2+ and Li + . Among them, in the leaching solution, the concentration of sulfuric acid is 2.5 M, and the volume percentage content of hydrogen peroxide is 6%; the solid-liquid ratio of the leaching solution to the pretreated positive powder 3 is 15 g / L, the temperature of the leaching treatment is 60 °C, and the time of the leaching treatment is 120 min; S5. For the selective precipitation method of the leaching solution, extraction and separation are carried out to obtain manganese dioxide, cobalt oxalate, nickel dimethylglyoxime, and lithium carbonate, so as to realize the separation and recovery of manganese, cobalt, nickel, and lithium in the cathode material of the lithium battery. Specifically, it includes: S501. Add the leaching solution obtained in S4 and potassium permanganate into the reaction vessel, then place the reaction vessel on a magnetic stirrer, set the heating temperature to 60 °C, the stirring speed to 200 r / min, react for 0.5 h, keep warm and age for 1 h, then filter using a suction filtration instrument to obtain the first precipitate and the first filtrate. After filtration, rinse the reaction vessel and the first precipitate with hot water 3 - 4 times, and incorporate the rinsing solution into the first filtrate; S502. Dissolve nickel dimethylglyoxime (DMG) powder in absolute ethanol and add it to the reaction vessel together with the first filtrate obtained in S501, and use NaOH solution or dilute H 2 SO 4 solution to adjust the pH value of the solution to 3. Then place the reaction vessel on a magnetic stirrer, set the heating temperature to 60 °C, the stirring speed to 200 r / min, react for 0.5 h, keep warm and age for 1 h, then filter using a suction filtration instrument to obtain the fifth precipitate and the fifth filtrate. After filtration, rinse the reaction vessel and the fifth precipitate with distilled water 3 - 4 times, and incorporate the rinsing solution into the fifth filtrate; The physical diagram of the obtained fifth precipitate is as Figure 28 shown. The fifth precipitate is pink nickel dimethylglyoxime powder; The XRD analysis of the fifth precipitate is as Figure 29 shown; From Figure 29 analysis, it can be seen that the peak positions and intensities are close to the standard card, indicating that the crystal form of the nickel dimethylglyoxime generated in the experiment is complete. The peak shape of the XRD pattern is narrow and high, indicating that the crystallinity of the sample is high, the diameter is large, and there are no impurity peaks, indicating that the purity of the generated nickel dimethylglyoxime is relatively high; S503. Adjust the pH value of the fifth filtrate obtained in S502 to 6.5, then add a mixed extractant, shake for 8 min, let it stand for liquid separation to obtain an oil phase and an aqueous phase containing Co 2+ to achieve the separation of Co 2+ from Ni 2+ , Li + . After extraction, use 1.5 M sulfuric acid solution to back-extract the oil phase containing Co 2+ . The ratio of the oil phase to the aqueous phase is 1:1, and the shaking time is 8 min, so that Co 2+ enters the aqueous phase from the organic phase to obtain an aqueous phase containing Co 2+ ; Among them, the extractant is a mixed extractant with a volume ratio of P507 extractant to sulfonated kerosene of 1:4, and the mixed extractant has been saponified before use; The oil-water ratio (the volume ratio of the extractant to the first filtrate) is 1:1; S504. The Co-containing 2+The aqueous phase is placed in a reaction vessel, and dilute sulfuric acid or sodium hydroxide solution is added to adjust the pH to neutral. Then sodium oxalate solution is added. Next, the reaction vessel is placed on a magnetic stirrer, with the temperature set at room temperature and the stirring speed at 200 r / min. After reacting for 0.5 h, it is aged for 1 h. Then it is filtered using a suction filtration instrument to obtain the sixth precipitate and the sixth filtrate. After filtration, the reaction vessel and the sixth precipitate are rinsed 3 - 4 times with ultrapure water, and the rinsing liquid is combined into the sixth filtrate; among them, the addition amount of sodium oxalate is based on Co 2+ in the aqueous phase containing Co 2+ , and n[C 2 O 4 2- : n(Co 2+ ) is 1.1:1; The physical diagram of the obtained sixth precipitate is as shown in Figure 6 . The sixth precipitate is dried in an oven at 50 °C, and finally pink cobalt oxalate powder is obtained; S505. The aqueous phase in S503 is placed in a reaction vessel, and sodium carbonate solution is added. Then the reaction vessel is placed on a magnetic stirrer, with the temperature set at room temperature and the stirring speed at 200 r / min. After reacting for 0.5 h, it is aged for 1 h. Then it is filtered using a suction filtration instrument to obtain the seventh precipitate and the seventh filtrate. After filtration, the reaction vessel and the seventh precipitate are rinsed 3 - 4 times with ultrapure water at 90 °C, and the rinsing liquid is combined into the seventh filtrate; The physical diagram of the obtained seventh precipitate is as shown in Figure 10 . The seventh precipitate is white lithium carbonate powder.

[0056] Example 11 In this example, the effect of the addition amount of dimethylglyoxime (DMG) on the Ni 2+ precipitate was studied. The steps and parameter conditions in the remaining S1, S2, S3, S4, S501, and S502 were the same as those in Example 10. Each time the obtained fifth filtrate was fixed to 100 mL, and the nickel, cobalt, and lithium contents in it were tested using ICP-MS, and the precipitation rates of nickel, cobalt, and lithium were calculated. Each group of experiments was carried out in three parallel experiments, and the results are as shown in Figure 30 .

[0057] It can be analyzed from Figure 30 that when n(DMG: Ni 2+ ) = 1.6, the precipitation rate of Ni 2+ is 79.9%. As the addition amount of DMG increases, the precipitation rate of Ni 2+ also increases. When n(DMG: Ni 2+ ) = 2, the precipitation rate of Ni 2+ increases to 99.17%, almost completely precipitated, while the loss rates of lithium and cobalt are 0.43% and 0.8% respectively. As the molar ratio of the two continues to increase, Ni 2+The precipitation rate no longer increases significantly.

[0058] Example 12 In this example, the effect of pH on the precipitation of Ni 2+ was studied. The steps and parameter conditions in the remaining S1, S2, S3, S4, S501, and S502 were the same as those in Example 10. Each time the obtained fifth filtrate was fixed to 100 mL, and the nickel, cobalt, and lithium contents were tested using ICP-MS, and the precipitation rates of nickel, cobalt, and lithium were calculated. Each group of experiments was carried out in triplicate, and the results are as Figure 31 shown.

[0059] From Figure 31 analysis, it can be seen that when pH = 1, the precipitation rate of Ni 2+ is 74.47%. As the pH increases, the precipitation rate of Ni 2+ also increases. This is because a low H + concentration is beneficial to the forward progress of reaction 4.10. When pH = 3, the precipitation rate of Ni 2+ is 99.17%, and the loss rates of lithium and cobalt are 0.43% and 0.8% respectively. As the pH continues to increase, the increase in the precipitation rate of Ni 2+ is not significant, while the loss rate of Co 2+ slightly increases. This is because a small part of Co 2+ is precipitated to form Co(OH) 2 , resulting in a decrease in the Co 2+ concentration.

[0060] Control Example 1 In this example, Na 2 S 2 O 8 was used to replace KMnO 4 , and the effect of the addition amount of Na 2 S 2 O 8 on the precipitation effect of Mn 2+ was studied. The steps and parameter conditions in the remaining S1, S2, S3, S4, and S51 were the same as those in Example 1. Each time the obtained first filtrate in S51 was fixed to 100 mL, and the nickel, cobalt, manganese, and lithium contents were tested using ICP-MS. Each group of experiments was carried out in triplicate, and the test results are as Figure 32 shown.

[0061] From Figure 32 analysis, it can be seen that on the premise of maintaining the pH of the original leaching solution unchanged, increasing the dosage of sodium persulfate can improve the Mn 2+The precipitation rate is not much help. Although the manganese content is slightly reduced, the precipitation rate of manganese is only about 20% even if the dosage is far more than the theoretical value. This is because the pH of the system is too low and the H + The content will inhibit the progress of reaction 4.2 and is not conducive to the 2+ of precipitation.

[0062] So in n[S 2 O 8 2- ]:n[Mn 2+ ]=1.75, the pH of the system was increased, and the effect of pH change on Mn 2+ The test results are as follows: Figure 33 shown.

[0063] from Figure 33 It can be seen from the analysis that when the dosage of sodium persulfate is constant, increasing the pH of the system is indeed beneficial to Mn 2+ When pH = 2, the manganese concentration is 20.13 μg / L. As the pH increases to 7, the manganese concentration drops to 8.13 μg / L. At the same time, it can be observed that the weight of the precipitate increases significantly. However, it is worth noting that with the increase of pH, except for Mn 2+ S 2 O 8 2- In addition to the precipitate, Ni 2+ and Co 2+ The concentration of Ni 2+ and Co 2+ The concentrations of Ni and Ni were 51.45 μg / L and 19.16 μg / L, respectively. When pH = 7, the concentrations of Ni and Ni dropped to 49.92 μg / L and 17.86 μg / L, respectively. This is because as the pH increases, Ni 2+ and Co 2+ It is precipitated in the form of hydroxide, and the generated nickel hydroxide and cobalt hydroxide will become impurities and mix into the manganese dioxide precipitation, reducing the purity of the product. 2+ A higher pH is required, which will cause nickel hydroxide and cobalt hydroxide to be precipitated at the same time, reducing the purity of manganese dioxide. Therefore, sodium persulfate is used to oxidize and precipitate Mn 2+ This approach is not feasible in this system.

[0064] In summary, the recycling method of waste ternary lithium batteries of the present invention effectively avoids potential environmental pollution during the treatment of waste batteries through the discharging and disassembly steps. By removing the binder with an organic solvent and removing the conductive agent by flotation, the positive electrode material can be efficiently separated, thereby improving the recovery rate of metal resources. The selective precipitation method is used to extract and separate the leaching solution, and manganese, cobalt, nickel, and lithium can be precisely separated to achieve the effective recovery of these precious resources. Through the above steps, high-purity manganese dioxide, cobalt oxalate, nickel salt, and lithium carbonate can be obtained, and these products can be used in the production of new battery materials or other industrial applications. This method not only reduces environmental pollution but also recovers valuable metal resources, having good economic and social benefits and having the value of popularization and application in the field of waste ternary lithium battery recycling technology.

[0065] The above embodiments are only preferred embodiments given to fully illustrate the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or transformations made by those skilled in the art on the basis of the present invention are within the protection scope of the present invention.

Claims

1. A method for recycling waste ternary lithium batteries, characterized in that: The following steps are involved: S1. Discharge and disassemble the used batteries to obtain positive electrode sheets; S2, removing the binder on the positive electrode sheet by using an organic solvent and then separating to obtain a positive electrode current collector and an initial positive electrode powder; S3, removing the conductive agent in the initial positive electrode powder by flotation method to obtain pretreated positive electrode powder; S4, using a mixture of an acid and an oxidant as a leaching solution, placing the pretreated positive electrode powder in the leaching solution for leaching treatment to obtain a leaching solution containing Mn 2+ 、Co 2+ 、Ni 2+ and Li + ; S5. The leaching solution is subjected to selective precipitation to extract and separate to obtain manganese dioxide, cobalt salt, nickel salt and lithium salt, so as to achieve separation and recovery of manganese, cobalt, nickel and lithium in the positive electrode material of lithium battery.

2. The method for recycling waste ternary lithium batteries according to claim 1, characterized in that: The S5 includes: S51, adding potassium permanganate to the leaching solution, stirring and reacting under a first temperature condition, keeping the temperature for aging, filtering, and obtaining a manganese dioxide precipitate and a first filtrate; S52, adjusting the pH value of the first filtrate to neutral, adding a mixed extractant, shaking, and standing to obtain a solution containing Co 2+ The oil phase and Ni 2+ and Li + The aqueous phase contains Co 2+ The oil phase was stripped to obtain the 2+ The mixed extractant is a mixture of P507 extractant and sulfonated kerosene; S53, adjust the content of Co 2+ The aqueous phase was neutralized, sodium oxalate solution was added, stirred for reaction, formed, filtered, and cobalt oxalate precipitate was obtained; 2+ and Li + Add sodium hydroxide solution to the aqueous phase, stir to react, form, and filter to obtain nickel hydroxide and a third filtrate; S54, adding sodium carbonate solution to the third filtrate, stirring to react, forming, filtering, and obtaining lithium carbonate precipitate.

3. The method for recycling waste ternary lithium batteries according to claim 2, characterized in that: In the S51, potassium permanganate and Mn in the leaching solution 2+ The molar ratio is 1~2; And / or, in S51, the first temperature is 50-70°C.

4. The method for recycling waste ternary lithium batteries according to claim 2, characterized in that: In the S53, sodium oxalate and Co 2+ The molar ratio of the aqueous phase is n[C2O4 2- ]:n[Co 2+ ] is calculated as 0.8~1.2; And / or, in said S53, to the Ni 2+ and Li + Add sodium hydroxide solution to the aqueous phase to make the pH value of the solution 8-12; And / or, in said S54, sodium carbonate and Li in the third filtrate + The molar ratio of n[CO3 2- ]:n[Li + ] is calculated as 0.5~0.

9.

5. The method for recycling waste ternary lithium batteries according to claim 1, characterized in that: The S5 includes: S501, adding potassium permanganate to the leaching solution, stirring and reacting under a first temperature condition, keeping the temperature for aging, filtering, and obtaining a manganese dioxide precipitate and a first filtrate; S502, dissolving dimethylglyoxime (DMG) in ethanol, then adding the first filtrate, adjusting the pH to acidic, stirring the reaction, keeping warm for aging, and filtering to obtain dimethylglyoxime nickel precipitate and the fifth filtrate; S503, adjusting the pH value of the fifth filtrate to neutral, adding a mixed extractant, shaking, and standing to obtain a solution containing Co 2+ The oil phase and the Li + The aqueous phase contains Co 2+ The oil phase was stripped to obtain the 2+ The mixed extractant is a mixture of P507 extractant and sulfonated kerosene; S504, adjust the content of Co 2+ The aqueous phase is heated to neutrality, sodium oxalate solution is added, stirred for reaction, formed, filtered, and cobalt oxalate precipitate is obtained; S505, to contain Li + Add sodium carbonate solution to the aqueous phase, stir to react, and filter to obtain lithium carbonate precipitate.

6. The method for recycling waste ternary lithium batteries according to claim 5, characterized in that: In S501, potassium permanganate and Mn in the leaching solution 2+ The molar ratio is 1~2; And / or, in S501, the first temperature is 50-70° C.; And / or, in said S502, the molar ratio of dimethylglyoxime (DMG) to the first filtrate is n[DMG]:n[Ni 2+ ] is calculated as 1.6~2.4; And / or, in S502, the pH value is 1-5.

7. The method for recycling waste ternary lithium batteries according to claim 5, characterized in that: In the S504, sodium oxalate and Co 2+ The molar ratio of the aqueous phase is n[C2O4 2- ]:n[Co 2+ ] is calculated as 0.8~1.2; And / or, in said S505, sodium carbonate and containing Li + The molar ratio of the aqueous phase is n[CO3 2- ]:n[Li + ] is calculated as 0.5~0.

9.

8. The method for recycling waste ternary lithium batteries according to claim 1, characterized in that: In S2, the organic solvent is selected from dimethylacetamide (DMAC), and the solid-liquid ratio of the positive electrode sheet to dimethylacetamide (DMAC) is 25-45 g / L; And / or, in S2, the adhesive on the positive electrode sheet is removed with the assistance of ultrasound, the power of the ultrasound is 800-900 W, and the time of the ultrasound is 30-110 min.

9. The method for recycling waste ternary lithium batteries according to claim 8, characterized in that: The S2 also includes recovering the dimethylacetamide (DMAC) solution separated after removing the binder on the positive electrode sheet with an organic solvent. The recovery method is: distilling the dimethylacetamide (DMAC) solution at a temperature of 175-185° C. to obtain a dimethylacetamide (DMAC) distillate, and the dimethylacetamide (DMAC) distillate is circulated to remove the binder on the positive electrode sheet.

10. The method for recycling waste ternary lithium batteries according to claim 1, characterized in that: In S3, dibromomethane is used as a flotation agent to remove the conductive agent in the initial positive electrode powder.

Citation Information

Patent Citations

  • Method for recovering valuable metal from high nickel lithium ion battery cathode scrap

    CN109055746A

  • Method for recycling nickel-cobalt-manganese-lithium from waste power lithium ion battery black powder

    CN111519031A

  • Method for separating and recycling nickel, cobalt, manganese and lithium from waste ternary lithium battery

    CN114717419A

  • Industrial recovery processing method suitable for various waste lithium batteries

    CN116315234A

  • Method for recycling waste ternary lithium ion battery

    CN117673536A

Cited By

  • Recovery method and application of nickel, cobalt, manganese and lithium in ternary black powder leaching purification liquid

    CN122256723A